PENGARUH RESERVASI MELALUI ONLINE TRAVEL AGENT DAN OFFLINE TRAVEL AGENT TERHADAP TINGKAT HUNIAN KAMAR - Ni Made Suniarti; Ni Nyoman Menuh (Forum Manajemen, 2019)
Room bookings can be done through online travel agents or offli ne travel agents where these both agents can offer attractive offers both in terms of price and benefits obtained by the customer. The purpose of this research is to knowing the effect of reservations through online travel agents and offline travel agents on the level of room occupancy. The results of this research indicate that based on the results of the F-test there is a significant and significant effect between reservation through online travel agent and offline travel agent to the level of room occupancy. Based on the partial calculation between the variables X1 and Y there is a significant and significant influence between reservations through online travel agents on the level of room occupancy. The variables X2 and Y have a significant and significant influence between reservations through offline travel agents partially on the level of room occupancy.